Republic of Armenia : Report on Observance of Standards and Codes-Data Module and Detailed Assessments Using the Data Quality Assessment Framework. (IMF Staff Country Reports; Country Report ;, 2002)
This report on the Observance of Standards and Codes provides a review of Armenia's data dissemination practices against the IMF's General Data Dissemination System (GDDS), complemented by an assessment of the quality of the national accounts, government finance, monetary, and balance-of-payments statistics. The report includes an overview of the GDDS and an assessment of Armenia's data dissemination practices against the Standard, and presents a summary assessment of the quality of the principal macroeconomic datasets. The coverage, periodicity, and timeliness for macroeconomic data in Armenia are also summarized.